Analisis Pemetaan Kesesuaian Ujian Keterampilan Klinis di Program Studi Kedokteran di Bali - Giri, Made Kurnia Widiastuti; Lasmawan, I Wayan; Putra , Adnyana (Jurnal Pendidikan Indonesia, 2022)
The learning process for students in the faculty of medicine has some objectives according to cognitive and skill. Especially for skills, some indicators were listed in a form of clinical skills assessment. Thus, indicators in the assessment of clinical skills were set based on established competency standards. Clinical skills examination was designed and implemented by health programs including medical science study programs. The health sciences study program should carry out learning with uniformity of patterns in the applied curriculum. This study to analyze the problems in conducting clinical examination on faculty of medicine. The results of this studied obtain a complete description of the needs in implementation of the Objective Structured Clinical Skills Examination (OSCE) for medical study programs with a descriptive qualitative method as an initial step in developing the OSCE exam model that aims to improve the competency abilities of clinical skills of students. This research presents descriptive qualitative data in a structured way in presenting data obtained through narrative stages of the preparation, implementation and evaluation of OSCE implementation. As the conclusion of this research, there was no similar pattern between medical study programs due to the absence of curriculum review activities so that uniformity in the implementation of OSCE cannot be carried out optimally. This study provides further recommendations to medical study programs to conduct an associate relationship in curriculum review because by reviewing the competencies of each graduate from a different university medical study program will be in the equivalent category.